The politics of religious commodification: Representation of power in the Cikande halal industrial zone - Ikhsan Ahmad; Asep Abdul Sahid; Agus Ahmad Safei (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the Banten Provincial Government's halal discourse in press releases, social media, and Cikande Halal Industrial Zone (KIHC) promotions (2019–2024) using Norman Fairclough’s Critical Discourse Analysis (CDA). Findings reveal halal discourse as a power apparatus that commodifies religion, blending religious lexicon (“halal,” “shariah,” “blessing”) with economic metaphors (“global hub,” “qiblat”) to legitimize industrial modernity. At textual and discursive levels, the state circulates narratives via institutional channels, fostering inevitability around halal industrialization and replacing coercion with persuasion. Socially, it forges a state-religion-capital triad, yielding “dual legitimacy”—moral via religious symbols, economic via investment promises—while crafting market-oriented pious consumers, sidelining justice, labor, and ecology. The study advances scholarship on religious commodification, state hegemony, and halal political economy, portraying halal discourse as governmentality merging morality and markets in Indonesia.